PERANAN E-GOVERNMENT DALAM PELAYANAN PUBLIK KECAMATAN KOTA AGUNG (Studi kasus : E-Government Kabupaten lahat) - Iski Meidiansyah; Darius Antoni; Muhamad Akbar (Jurnal Bina Komputer, 2019)
The use of E-Government becomes an inseparable part of public activity. Therefore, the development and improvement of E-Government should always be done considering the current technology has been developed, especially in the interface or interface. In an effort to achieve the efficiency of the role of e-government in public service using RBV theory is important enough, let alone related to the satisfaction of use, the feasibility of website display, information system satisfaction, and others. The e-government Portal Website is used as a product, public service and community use satisfaction in Lahat District. This website is also used as a means of agency information. Review of Website utilization e-government portal needs to be done to measure from user satisfaction level. To measure the level of user satisfaction / Website users. Lahat District as one of the local Governments in South Sumatra has been using E-Government in the performance process. The purpose of this research is to generate a good usability value, so that later will provide input to Lahat Regency about the development of E-Government. The method in this research is action research using descriptive research with quantitative approach. Testing is done by Partial Least Square method, as a benchmark to generate public satisfaction. Based on the discussion then in this study obtained the conclusion that the e-Government interface of Lahat Regency currently does not reach the ideal usability level then the researcher gives the proposal to provide training to the public